Are the mutans streptococci still considered relevant to understanding the microbial etiology of dental caries? - Jeffrey A. Banas; David R. Drake (BMC, 2018)
Abstract The mutans streptococci were once the primary focus of research dedicated to understanding the etiology of dental caries. That focus has now shifted to an emphasis on the ecological balances and complexities within the entirety of the plaque microbiome. Within that framework there are considerable differences of opinion regarding the importance and relative contributions of the mutans streptococci. This article explores the basis for the various viewpoints, the limitations of current knowledge, and the confounders that make it difficult to arrive at a consensus.